Trends in the competitive performance of the world’s strongest weightlifters before the xxxiii olympic games in paris = Тенденції змагальної діяльності найсильніших важкоатлетів світу напередодні ігор ХХХІІІ Олімпіади в Парижі : ст. - Оleshko, V. et. al.; Маrtyn, V.; Semeniv, B. (Львівський національний університет ветеринарної медицини та біотехнологій імені С. З. Ґжицького, 2024)
Background and Study Aim. The article aims to study the trends in the competitive performance of the world’s strongest weightlifters at the 2023 World Championship and to reveal the prospects for their further entry into the XXXIII Olympic Games in Paris = Мета. Вивчити тенденції змагальної діяльності найсильніших важкоатлетів світу на чемпіонаті світу 2023 року та визначити перспективи подальшого їх попадання на Ігри ХХХІІІ Олімпіади.
Keywords: physical culture and sports; weightlifters; фізична культура і спорт; важкоатлети